A Box Spread Test of the SET50 Index Options Market Efficiency: Evidence from the Thailand Futures Exchange - Jongadsayakul, Woradee (International Journal of Economics and Financial Issues, 2016)
This paper provides the box spread test of the SET50 index options market efficiency using daily data from October 29, 2012, through March 30, 2016. The results show that the market frictions imposed by the bid-ask spread, along with brokerage commissions, exchange fees, and interest on initial margin deposit, appear to have a significant effect on arbitrageurs' abilities to take advantage of the mispricing of the box spreads. When using bid-ask prices rather than closing prices, the box spread arbitrage opportunities drop to less than 1 percent, and none of them is persisted on the following trading day. Considering transaction costs, the results therefore confirm the internal options market efficiency in the SET50 index options market. However, the results do not provide support for the argument that the SET50 index options market efficiency improved over time. Keywords: Market Efficiency, Index Options, Box Spreads JEL Classifications: G13, G14